PKM PENDAMPINGAN PEMASARAN UMKM IKATAN PENGUSAHA AISYIYAH DI KOTA MALANG - Affan, Muhammad Wildan; Irawan, Dwi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2020)
Muhammadiyah has formed the Aisyiyah Entrepreneurs Association which aims to accommodate the entrepreneurial activities of Aisyiyah members. But in its implementation there are several obstacles that occur that greatly hinder the development of its business. Among them are poor organizational culture, the use of basic local wisdom materials for products produced quite a bit, as well as marketing that does not take advantage of technological advances to make online sales. Optimization of the IPAS community, namely providing solutions to the constraints that occur through appropriate training and marketing assistance using technological advances includes understanding the importance of good organization marked by creating organizational structures, conducting online sales training both in terms of products and in terms of packaging in in order to support marketing to be able to compete in a wider market.